2019
DOI: 10.1016/j.jclepro.2019.02.223
|View full text |Cite
|
Sign up to set email alerts
|

Raw metal needs and supply risks for the development of wind energy in Germany until 2050

Abstract: Facilitated by the environmental goals set by the government, wind turbines will be one of the main pillars of the future electricity production in Germany. In this paper, a comprehensive assessment of the future metallic raw material requirements for the development of the German wind energy sector was conducted, which is closely based on the current and future market conditions. Copper and dysprosium are identified as the most critical materials since they face the possibility of supply bottlenecks while bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…It was concluded that wind energy companies cannot find new loans when interest rates are high. Moreover, Shammugam et al [6] studied the supply risks for the development of wind energy in Germany until 2050 by using a regression methodology. It was determined that interest rate risks are one of the most significant risks for these projects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was concluded that wind energy companies cannot find new loans when interest rates are high. Moreover, Shammugam et al [6] studied the supply risks for the development of wind energy in Germany until 2050 by using a regression methodology. It was determined that interest rate risks are one of the most significant risks for these projects.…”
Section: Discussionmentioning
confidence: 99%
“…Besides this, the increasing interest rate will harm the customers and suppliers of the company. This will cause the wind power company to experience difficulties in the supply chain [6].…”
Section: Literature On the Risk Factors Of Wind Energy Investmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…This issue has aroused worldwide concern. For the German wind industry, Shammugam et al (2019) sees copper and dysprosium as the most critical materials for development, both of which clearly exceed Germany's quota for renewable energy technologies and will face stiff competition from other sectors for access to raw materials. In the United States, renewable energy (mainly wind and solar) is particularly constrained by Te and Dy (Nassar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%